Recovery of BMD after pregnancy and breastfeeding : a 10-yr prospective observational study of 25-yr-old women - Egund, Lisa; Malmgren, Linnea ; 0000-0003-3296-7083; Woolf, Anthony D; McGuigan, Fiona E ; 0000-0002-8033-9981; Akesson, Kristina E (Journal of Bone and Mineral Research, 2025)
Pregnancy and lactation require large amounts of calcium potentially depleting the young adult bone. This study investigated BMD and fluctuations of BMD resulting from parity and lactation in the PEAK-25 cohort, a prospective observational study of women all aged 25 at inclusion and 35 at follow-up. The analyses use women who were nulliparous at baseline and parous (n = 573) or nulliparous (n = 177) 10-yr later. Parity, regardless of number of pregnancies, had no negative impact, indeed spine BMD at age 35 was higher (2.1%; p = .043). Likewise, BMD did not differ in women who breastfed, were non-lactating or nulliparous. Even the cumulative duration of breastfeeding did not make a difference. Overall, and regardless of parity, in the cohort, by age 35 BMD is already decreasing, with overall losses at femoral neck (∆ - 3.4%) and total hip (∆ - 2.7%); although not spine (∆0.9%). Yet, BMD fluctuations associated with pregnancy, lactation and weaning were seen in the short term. Comparing those pregnant more than 24 m with those less than 24 m prior to DXA, BMD was lowest in women more recently pregnant (FN -2.2%, TH -2.7%). Women pregnant within 12 m had 4% lower TH BMD compared to more than 36 m (p = .054, padj = 0.032). Cumulative duration of breastfeeding was associated with bone loss, particularly beyond 15 mo (FN ∆-4.3%; TH ∆-3.7%) and lower spine BMD accretion. Despite such periods of loss, BMD recovers, evidenced by time-from-weaning to DXA. Women weaning within 6 mo of measurement had lower FN BMD compared to those where the interval was more than 24 mo (6.6% vs 1.7%, p < .001). In conclusion and despite repeated fluctuations in BMD resulting from the physiological demands of multiple pregnancies and periods of breastfeeding, BMD recovers and ultimately doesn't differ from that of identically aged women without children.
© The Author(s) 2025. Published by Oxford University Press on behalf of the American Society for Bone and Mineral Research.
Keywords: BMD; lactation; parity; women; bone loss